Poorer divided attention in children born very preterm can be explained by difficulty with each component task, not the executive requirement to dual-task. Issue 5 (4th July 2017) - Delane, Louise; Campbell, Catherine; Bayliss, Donna M.; Reid, Corinne; Stephens, Amelia; French, Noel; Anderson, Mike
ABSTRACT: Children born very preterm (VP, ≤ 32 weeks) exhibit poor performance on tasks of executive functioning. However, it is largely unknown whether this reflects the cumulative impact of non-executive deficits or a separable impairment in executive-level abilities. A dual-task paradigm was used in the current study to differentiate the executive processes involved in performing two simple attention tasks simultaneously. The executive-level contribution to performance was indexed by the within-subject cost incurred to single-task performance under dual-task conditions, termed dual-task cost . The participants included 77 VP children (mean age: 7.17 years) and 74 peer controls (mean age: 7.16 years) who completed Sky Search (selective attention), Score (sustained attention) and Sky Search DT (divided attention) from the Test of Everyday Attention for Children. The divided-attention task requires the simultaneous performance of the selective- and sustained-attention tasks. The VP group exhibited poorer performance on the selective- and divided-attention tasks, and showed a strong trend toward poorer performance on the sustained-attention task. However, there were no significant group differences in dual-task cost. These results suggest a cumulative impact of vulnerable lower-level cognitive processes on dual-tasking or divided attention in VP children, and fail to support the hypothesis that VP children show a separable impairment in executive-level abilities.